(untitled) (Ianna Journal of Interdisciplinary Studies,ISSN(O):2735-9891,ISSN(P):2735-9883, 2024)
Employees working in organizations must also be concerned about the environment, as they care about the environment.Employee participation is the process of providing opportunity for the employees to participate in the decision-making process and it is a part of the process of empowerment in the workplace.Green citizen participation employees influenced on Engage Employees, Conserve energy, Reduce waste, Environmental problem-solving, Environmental awareness and Proper utilization of resources, Finally, it concludes thatGreen citizen participation indicates that reduces waste and conserves energy from the employee’s leads to organizational performance effectively in IT sector.